PHARMACOKINETIC PROFILE AND INCURRED ESOMEPRAZOLE SAMPLE STABILITY IN PLASMA USING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - PHOTODIODE ARRAY - HARAHAP, YAHDIANA; FARIS, AHMAD; SUNARSIH (International Journal of Applied Pharmaceutics, 2019)
Objective: Esomeprazole (ESO) is one of the proton-pump inhibitors and is used to treat gastroesophageal reflux. It is sensitive to low pH, heat, moisture, and oxidation, which often means that ESO in clinical samples is degraded at the time of storage, affecting analysis results. This study aimed to analyze the in vivo stability of ESO in subjects’ plasma samples by testing the incurred sample stability (ISS) of ESO in plasma following 7, 14, and 28 days of storage at two concentrations close to Cmax and one concentration in the elimination phase. Methods: Samples were analyzed using high-performance liquid chromatography with a C18 column with detection at 300 nm using a photodiode array detector. Lansoprazole was used as an internal standard. Results: The ESO pharmacokinetics profile in the plasma samples yielded the values of Cmax 704.57–1425.85 ng/mL; tmax is 2.25 h; and AUC0-t is 2444 ng.h/mL. ISS testing of plasma samples values were 6.50%, 5.73%, and 4.57% on first Cmax concentration; 3.55%, 4.84%, and 3.68% on 2nd Cmax concentration; and 4.04%, 4.80%, and 4.98% on elimination phase concentration. Conclusion: ISS testing results of plasma samples from six healthy subjects who were administered doses of 40 mg of ESO stored for 28 days showed that it fulfilled the acceptance criteria (<20%) of the 2011 EMEA Bioanalytical Guidelines with a %diff value in all incurred samples of 6.5%.